IMPLEMENTASI PROGRAMMABLE LOGIC CONTROL (PLC) OMRON CP1E PADA SISTEM KENDALI MOTOR INDUKSI STAR-DELTA UNTUK KEBUTUHAN INDUSTRI - Firdaus Yudha Hartawan; Mia Galina (P3M Politeknik Negeri Indramayu, 2022)
The star delta control circuit is a sistem used to control an induction motor with a minimum power of 7.5 kW. Most industries still use conventional control sistems or without the use of PLC (Programmable Logic Controller). The purpose of this research is to apply PLC (Programmable Logic Controller) OMRON CP1E E-30-DR-A as an automatic control sistem on a star delta induction motor, whose working sistem is designed using a ladder diagram. In this study also added a safety sistem that will provide more protection to the components and the sistem as a whole. The main components of the PLC used have a working voltage range of 100 - 240 VAC. The design of this sistem uses two main sistems, namely a control sistem consisting of an ON/OFF pushbutton with a working voltage of 24 VDC. The power sistem consists of a contactor with a working voltage at terminal A1 of 220 VAC and a manual motor starter as a safety for the induction motor. The results of testing this sistem show that all sistem components can function properly with a supply voltage according to specifications, namely the working voltage at the L1 PLC terminal is 241.1 VAC, the voltage on the ON pushbutton control sistem is 24.53 VDC and the OFF pushbutton is 24,6 VDC. The working voltage on the power sistem at the contactor A1 terminal is 241.1 VAC.